Assessment of occupational health risk for workers employed at contemporary rubber production - E.T. Valeeva; L.K. Karimova; R.R. Galimova; N.A. Muldasheva; A.A. Distanova (Analiz Riska Zdorovʹû, 2020)
The paper dwells on the results obtained in assessing occupational health risk for workers employed at rubber production; the assessment was based on examining both a priori and a posteriori parameters. It was shown that workers were exposed to a set of factors related to working environment and labor process including hazardous chemicals, in-plant noise, adverse microclimate, as well as physical overloads. Chemical factor played the leading role as there were various chemicals in working area air such as benzene in concentrations equal to 1.2–3.0 MPC (maximum single concentration amounted to 4 MPC); di-chloromethane in concentrations equal to 0.2–1.5 MPC average monthly (maximum single ones equal to 2 MPC). Overall work-ing conditions assessment for workers with different occupations employed at rubber production belonged to 3.2 hazard category. Workers who glued parts of articles together ran high risks of occupational diseases; risks were average for spreading machine operators and vulcanizers. Total occupational diseases index amounted to 0.83 for workers who glued articles and to 0.80 for spreading machine operators and vulcanizers and it meant that occupational risk was high. We also revealed that certain diseases were occupationally induced and the dependence was significant; it was true for segmental disorders in the vegetative nervous system with sensitivity failure in hands for gluing workers (RR – 10.3, CI = 95 %, EF – 90 %), musculoskeletal system diseases (RR – 2.5, CI = 95 %, EF – 55 %), and skin and subcutaneous tissue diseases for spreading machine operators and vulcanizers (RR – 2.6, CI = 95 %, EF – 61 %). We ranked occupations as per related occupational health risks and revealed that workers who glued articles had the highest integral occupational risk assessment. Occupational risk assessment gave grounds for developing a risk-oriented program that included priorities and ways to prevent damage to health of workers employed at rubber production such as managerial and medical and prevention activities as well as social support and protection.